Classifying Aerosol Particle Size Using Polynomial Coefficient of Aerosol Optical Depth–Wavelength Relationship - Dyi-Huey Chang (IEEE ICACEH 2024, 2025)
Aerosols are composed of suspended solid or liquid particles and interact with solar radiation through absorption, refraction, and scattering, influencing climate variability. The Ångström exponent (α) is commonly used to differentiate particle sizes, but its relationship with aerosol optical depth (AOD) and wavelength (λ) is non-linear. This relationship is modeled using higher-order polynomial expressions in this study based on the AOD data from the AErosol RObotic NETwork (AERONET). In the model, polynomial coefficients are used to effectively classify aerosol types, such as dust and biomass-burning aerosols, with a strong correlation among coefficients of the same order. Such a close correlation among the coefficients of the same polynomial order is attributed to a large variability. The coefficients of the same order exhibit a scaled relationship, where scaling factors are expressed as a function of wavelength.